2022
DOI: 10.1097/cco.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the methionine−methionine adenosyl transferase 2A−S-adenosyl methionine axis for cancer therapy

Abstract: Purpose of reviewIn this review, we summarize the biological roles of methionine, methionine adenosyl transferase 2A (MAT2A) and S-adenosyl methionine (SAM) in methylation reactions during tumorigenesis. Newly emerged inhibitors targeting the methionineÀMAT2AÀSAM axis will be discussed. Recent findingsSAM is the critical and global methyl-donor for methylation reactions regulating gene expression, and in mammalian cells, it is synthesized by MAT2A using methionine. Recent studies have validated methionine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…As shown in Table 1, we utilized pyrido [2,3d]pyrimidine as a bicyclic core structure and screened several tricyclic substituents (4−11). Gratifyingly, substitution with methyl-tetrahydrobenzo [4,5]imidazo[1,2-a]pyrazine resulted in a compound (8) with a MAT2A enzymatic inhibition IC 50 of 18 nM and HCT116(MTAP−/−) cell proliferation inhibition IC 50 of 52 nM, which were significantly better than those of AG-270 (cell IC 50 = 244 nM), which is under evaluation in clinical trials (Figure S1). AGI-43192 is a promising clinical candidate developed by Agios Pharmaceuticals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Table 1, we utilized pyrido [2,3d]pyrimidine as a bicyclic core structure and screened several tricyclic substituents (4−11). Gratifyingly, substitution with methyl-tetrahydrobenzo [4,5]imidazo[1,2-a]pyrazine resulted in a compound (8) with a MAT2A enzymatic inhibition IC 50 of 18 nM and HCT116(MTAP−/−) cell proliferation inhibition IC 50 of 52 nM, which were significantly better than those of AG-270 (cell IC 50 = 244 nM), which is under evaluation in clinical trials (Figure S1). AGI-43192 is a promising clinical candidate developed by Agios Pharmaceuticals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1 H NMR (500 MHz, chloroform-d) δ 8.76 (s, 1H), 7.79 (s, 1H), 7.41 (dd, J = 8.3, 2.0 Hz, 1H), 7.32 (s, 4H), 7.17 (d, J = 1.9 Hz, 1H), 6.86 (d, J = 8.3 Hz, 1H), 6.61 (t, J = 73.6 Hz, 1H), 4.56 (s, 2H), 4.21 (q, J = 7.1 Hz, 2H), 1.31 (t, J = 7.1 Hz, 3H), 1.19−1.11 (m, 2H), 1.09− 1.00 (m, 2H). 13 [4,5]imidazo [1,2-a]pyrazin-7-yl)pyrido [2,3-d]pyrimidin-7(8H)-one (8). Light yellow solid; 30% yield.…”
Section: -(4-(difluoromethoxy)phenyl)-7-ethoxy-3-(2-methyl-2h-indazol...mentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo models have shown that MAT2a knockdown reduced the growth and development of MTAP deficient tumor cells [19]. IDE397, a small molecule inhibitor of MAT2A, is under investigation as a part of a Phase 1 trial for advanced solid tumors with MTAP deletion [20].…”
Section: Discussionmentioning
confidence: 99%